Educational policies during the era of the Custodian of the Two Holy Mosques King Salman bin Abdulaziz to achieve the vision of the Kingdom of Saudi Arabia 2030: Analytical Study - Al-Otaibi, Faris Awaid; Al-Muntasheri, Aeydh Ahmad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the educational policies in the era of King Salman bin Abdulaziz to achieve the vision of the Kingdom of Saudi Arabia 2030, by presenting the educational policies that were issued at the level of the Ministry of Education, General Education, and Higher Education. And determining the extent of its relevance to the goals of the Kingdom of Saudi Arabia 2030 vision, and the strategic goals of the Ministry of Education. The study used the descriptive approach in the method of content analysis to describe the educational policies that were issued during the reign of King Salman bin Abdulaziz to achieve the vision of the Kingdom of Saudi Arabia 2030 as stated in official documents and documents. And analyzing it to clarify the extent of its relevance to the goals of the Kingdom of Saudi Arabia 2030 vision, and the strategic goals of the Ministry of Education. The two researchers concluded from this analysis that educational policies during the reign of King Salman bin Abdulaziz were closely related to all axes of the vision of the Kingdom of Saudi Arabia, where the greatest link was in the third axis (an ambitious nation) and its strategic goals, to which all eleven policies were linked with a rate of 0.47%, and then comes after it the second axis (a prosperous economy) and its strategic goals were 9 policies at a rate of 0.37%, and finally the link was with the first axis (a vibrant society) and its strategic goals were 5 policies at a rate of 0.16%. It was also related to all the strategic goals of the vision of the Kingdom of Saudi Arabia except for one goal, where it was highly correlated with five of the strategic objectives of the Ministry of Education, where the third objective achieved (11) recurrences with a rate of 0.19%, the second and fourth goals (10) iterations with a rate of 0.17%, the ninth goal (9) iterations with a rate of 0.15%, and the sixth goal achieved (8) iterations with a rate of 0.14%. Its correlation was moderate to two of the strategic goals of the Ministry of Education, namely, the first and seventh, which were repeated (4) with a rate of 0.07%, while it was weakly linked to two of the strategic goals of the Ministry of Education, as the eighth goal was achieved (3) iterations with a rate of 0.05%, while the fifth goal was not achieved as the number of its repetitions It was (0). Based on the results, the researchers presented a number of recommendations and proposals to strengthen the relationship between the strategic objectives of the Ministry of Education and link them to the objectives of the vision of the Kingdom of Saudi Arabia 2030, the most important of which are: The educational policy should be flexible and take the initiative when there is any need for modification or change in the educational systems to meet the educational problems and the demands and needs of the society, and the Ministry of Education should pay great attention to the education policy document in the Kingdom of Saudi Arabia, in terms of printing and publishing on its website, re-circulating it and drawing attention to it in the educational field.